Strategi Pengembangan Pendidikan NonFormal dalam Pengelolaan Hasil Hutan Berbasis Agroforestri melalui Program Sekolah Lebah Madu di Kepulauan Mentawai - Prayoga, Rendi; Falah, Nur; Fauzan, Muhammad Reza; Mardiansyah, Ramos; Rahmi, Lailatur (PAKAR Pendidikan, 2024)
Abstracts are written in two languages, namely English and Indonesian, a minimum of 150 - 250 words. Abstracts are written with Calisto MT 10, spaced 1 paragraph and italicized for abstract [english) consisting of research problems, objectives, metodes, results and discussions, and research conclusions. The abstract describes the research carried out so that it is useful and contributes to the development of science and technology in the field of education. Keywords are written in abstracts which are the substance of the research that has been carried out.